The Normans in the Mediterranean - Winkler, Emily A.; Fitzgerald, Liam (Brepols, 2021)
In both popular memory and in their own histories, the Normans remain almost synonymous with conquest. In their relatively brief history, some of these Normans left a small duchy in northern France to fight with Empires, conquer kingdoms, and form new ruling dynasties. This book examines the explosive Norman encounters with the medieval Mediterranean, <span class=